2009
DOI: 10.1016/j.jnucmat.2009.01.087
|View full text |Cite
|
Sign up to set email alerts
|

Carbon balance and deuterium inventory from a carbon dominated to a full tungsten ASDEX Upgrade

Abstract: The evolution of carbon/boron deposition and the deuterium inventory were determined during the transition from a carbon dominated to a full tungsten ASDEX Upgrade. In the carbon dominated machine about 17 g of carbon were deposited at the inner divertor and in remote areas during one standard discharge campaign. Main carbon sources were the ICRH antennae protection limiters in the main chamber. After coating these limiters with tungsten the carbon deposition decreased to 35 g. The remaining carbon originated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 26 publications
10
63
3
2
Order By: Relevance
“…Post-campaign analysis of C and B layers on PFC surfaces as well as D retention measurements allowed the characterisation of fuel retention over the C ¢ W PFC transition [4] [5]. Figure 1 shows a large reduction of C deposition in the inner divertor after W coating of the outer limiters, identifying these limiters as a dominant C source.…”
Section: Campaign Integrated Deposited Layers and Fuel Retentionmentioning
confidence: 99%
“…Post-campaign analysis of C and B layers on PFC surfaces as well as D retention measurements allowed the characterisation of fuel retention over the C ¢ W PFC transition [4] [5]. Figure 1 shows a large reduction of C deposition in the inner divertor after W coating of the outer limiters, identifying these limiters as a dominant C source.…”
Section: Campaign Integrated Deposited Layers and Fuel Retentionmentioning
confidence: 99%
“…AUG is a divertor tokamak which has switched progressively from a carbon to a tungsten [7] [8] for a detailed description of the machine configuration and operation). From [9] and [10], where particle balance is shown on a standard H mode discharge, a retention rate of 1.25-3.5×10 21 D/s can be deduced for a high density scenario (0.5 -1.4×10 22 D retained at the end of the 4s discharge respectively from…”
Section: Asdex Upgradementioning
confidence: 99%
“…8. The sample was exposed at the outer strike point of the tokamak ASDEX Upgrade to a uence of more than 3 × 10 25 D/m 2 [4]. The D concentration reaches about 10 at.% at the surface, most probably due to the formation of a thin hydrocarbon layer.…”
Section: Deuterium In Tungstenmentioning
confidence: 99%
“…Deuterium can penetrate in these materials up to depths of several tens to several hundreds of µm, where it is trapped at low concentrations [1,2]. It has been assumed that this deep penetration is an important process for the deuterium inventory in the tokamak Tore Supra [3], and it has been shown that deep penetration is dominating the remaining deuterium inventory in the all-tungsten tokamak ASDEX Upgrade [4]. In carbon materials this penetration is related to the porosity of the material, while in tungsten the di usion process is driven by the stress-eld induced by implanted deuterium [2].…”
Section: Introductionmentioning
confidence: 99%